The Saudi Thoracic Society Evidence-based guidelines for the diagnosis and management of chronic obstructive pulmonary disease - Hamdan Al-Jahdali; Riyad Al-Lehebi; Hani Lababidi; Faris F. Alhejaili; Yahya Habis; Waleed A. Alsowayan; Majdy M. Idrees; Mohammed O. Zeitouni; Abdullah Alshimemeri; Mohammed Al Ghobain; Ali Alaraj; Esam H. Alhamad (Annals of Thoracic Medicine)
The Saudi Thoracic Society (STS) developed an updated evidence-based guideline for diagnosing and managing chronic obstructive pulmonary disease (COPD) in Saudi Arabia. This guideline aims to provide a comprehensive and unbiased review of current evidence for assessing, diagnosing, and treating COPD. While epidemiological data on COPD in Saudi Arabia are limited, the STS panel believes that the prevalence is increasing due to rising rates of tobacco smoking. The key objectives of the guidelines are to facilitate accurate diagnosis of COPD, identify the risk for COPD exacerbations, and provide recommendations for relieving and reducing COPD symptoms in stable patients and during exacerbations. A unique aspect of this guideline is its simplified, practical approach to classifying patients into three classes based on symptom severity using the COPD Assessment Test and the risk of exacerbations and hospitalizations. The guideline provides the reader with an executive summary of recommended COPD treatments based on the best available evidence and also addresses other major aspects of COPD management and comorbidities. This guideline is primarily intended for use by internists and general practitioners in Saudi Arabia.